Проблемні питання визначення підслідності військових злочинів за новим КПК України - Бабич, А. А.; Бабич, А. А.; Babich, А. (My University, 2013)
The article is devoted to the general characteristics of criminal offenses in the armed forces and the determination of their suspects in the new Code of Criminal Procedure of 2012. The author substantiate the necessity of maintaining the operational units of the Military Service Law Enforcement Armed Forces of Ukraine and creation into this service of investigative units to investigate military crimes and common crimes committed by servicemen on military objects.
Бабич А. А. Проблемні питання визначення підслідності військових злочинів за новим КПК України / А. А. Бабич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 374-381.
Keywords: характеристика кримінальних правопорушень в Збройних Силах України; Кримінальний процесуальний кодекс України 2012 року.; оперативні підрозділи у Військовій службі правопорядку Збройних Сил України; слідчі підрозділи у Військовій службі правопорядку Збройних Сил України; характеристика уголовных правонарушений в Вооруженных Силах Украины; Уголовный процессуальный кодекс Украины 2012 года; оперативные подразделения в Военной службе правопорядка Вооруженных Сил Украины; следственные подразделения в Военной службе правопорядка Вооруженных Сил Украины; characterization of criminal offenses in the Armed Forces of Ukraine; The Criminal Procedural Code of Ukraine in 2012; operational units of the Military Service Law Enforcement Armed Forces of Ukraine; investigative units in the Military Service Law Enforcement Armed Forces of Ukraine